KONSEP ISLAM DAN MODERNITAS MOHAMMED ARKOUN Telaah Pemikiran Islam sebagai komparasi konsep Islam dan modernitas Nurcholis Madjid - Kulsum, Ummu; Subhan, Moh (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2015)
Many people translated Word of Islam, in to French by meaning "bow and is obedient" (Islam). This translation according to Arkoun is not at all correctness. The faithful is not bowing obedient before Allah; but he feels vibration love to Allah and wish to lean himself to what commanded by Him. Islam represents voluntary action as implicit in Him word of s-l-m, " becoming is peaceful, awake, intactly". Someone cannot run islam for the shake of others, and in consequence. Islam enforces confidence do not be enabled. Philosophic congeniality which constitute modernity more than simply historical congeniality and also sociology. Arkoun differentiated "material" and modernity "intellectual" or "cultural". First mean all sort of progress that happened at external frame of human being form, while secondly include cover method, analyzer, and intellectual attitude which give ability to be more comprehending reality. The Usage of material modernity and all its result relate to idea modernity form going into effect. Whereas according to Cak Nur, Islam is religion of al-hanifiyyat as-samha-religion which tends to to truth and full of tolerances. Like that picture of Islam religion of Ibrahim which is hanif. Cak Nur formulated that " modernization" meaning rationalization to obtain to get useful power in Thinking and work maximalyl, utilizing bliss of mankind, therefore, he said that " modernization" meaning think and work according to fitrah of sunnatullah (godlike law which is nature) sunnatullah have itself manifest in natural law, so that to be able to become modernly, human being have to understand applicable law in that nature (God command).